Analysis of patients' knowledge on risk factors of cardiovascular diseases and new technology of self-control this factors - especially with cholesterol - Staniszewska, Anna; Olejniczak, Dominik; Smoleńska, Elwira; Kielan, Aleksandra (Journal of Education, Health and Sport, 2017)
Many determinants of cardiovascular risk have been identified. Lack of knowledge about common risk factors of cardiovascular diseases could provoke their underestimation and confer further risk increase. New medical technology helps patient’s by self-care.